Antidiabetic effect of Gymnema sylvestre in Streptozotocin induced diabetes in rats - Shridhar, Pragathi B.; Rao, Suguna; Byregowda, Sonnahallipura M.; Satyanarayana, Mayasandra L.; Nagaraj, B. N.; Kamran, C. Ansar; Ayoub, Syed M.; Purushotham, Kondappa M. (Brazilian Journal of Veterinary Pathology, 2015)
The purpose of the study was to study the hypoglycemic effect of Gymnema sylvestre in streptozotocin induced diabetic rat model. G. sylvestre was administered at the dose rate of 50 and 100 mg/kg b w and was compared with standard hypoglycemic drug, glibenclamide for its anti hyperglycemic effect. There was improvement in various parameters such as body weight, haemoglobin, serum glucose, cholesterol, triglycerides, AST, ALT and antioxidant enzymes in all the treatment groups. G. sylvestre elicited dose dependent effect with 100 mg/kg b w being more effective in alleviating most of the diabetic clinical signs. The findings were clearly substantiated by histopathology and immunohistochemistry. In conclusion, G. sylvestre has significant antidiabetic effect at 100 mg/kg b w when administered daily for 45 days.